2021
DOI: 10.3389/fgene.2021.689097
|View full text |Cite
|
Sign up to set email alerts
|

The CPNE Family and Their Role in Cancers

Abstract: Lung cancer is the leading cause of cancer-related deaths worldwide. Despite significant advances in cancer research and treatment, the overall prognosis of lung cancer patients remains poor. Therefore, the identification for novel therapeutic targets is critical for the diagnosis and treatment of lung cancer. CPNEs (copines) are a family of membrane-bound proteins that are highly conserved, soluble, ubiquitous, calcium dependent in a variety of eukaryotes. Emerging evidences have also indicated CPNE family me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 69 publications
0
27
0
Order By: Relevance
“…Copines‐1 is a newly discovered soluble membrane‐binding protein 11,26 . Importantly, several studies have highlighted that CPNE1 is significantly overexpressed in various malignancies 6 . Recent evidence indicates that increased CPNE1 expression is correlated with tumor size, differentiation, and metastasis in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Copines‐1 is a newly discovered soluble membrane‐binding protein 11,26 . Importantly, several studies have highlighted that CPNE1 is significantly overexpressed in various malignancies 6 . Recent evidence indicates that increased CPNE1 expression is correlated with tumor size, differentiation, and metastasis in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Like other gene families, the CPNE family is also present throughout evolution, and nine CPNEs have been identified. Among them, 8 CPNEs (CPNE1–8) are found in mammals 6 . Copines‐1 (CPNE1) is a calcium‐dependent phospholipid‐binding protein that was first identified by Creutz in 1998, when he isolated annexin in Paramecium 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence has indicated that copine family members are involved in cancer development and progression. Tang summarized the biological properties of the copine family and their oncogenic roles in several cancers, including breast, colorectal, and non-small cell lung cancers 12 . The copine family of proteins perform different signal transduction functions, such as membrane transport, lipid messenger production, GTPase activation, protein phosphorylation, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Robust CPNE8 expression was detected in the prostate, heart, and brain, suggesting that CPNE8 might play an essential role in the regulation and development of the prostate 16 . CPNE family genes such as CPNE1 and CPNE3 , were closely related to tumorigenesis and progression 12 , 17 , 18 . However, there is limited knowledge regarding the roles and mechanisms of CPNE8 in carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%